The Impact of Interactive Video Learning Media on Fifth-Grade Students' Learning Interest in Integrated Science and Social Studies - Viorenica, Venny; Aprima, Desy (Papanda Publisher, 2025)
Students' learning interest plays a crucial role in determining educational success, yet conventional instructional methods often fail to engage elementary students effectively. This study investigated the effect of interactive video learning media on fifth-grade students' learning interest in Integrated Science and Social Studies (IPAS) instruction. Employing a descriptive quantitative design, the study was conducted at SD Negeri Tepung Sari, a rural elementary school with limited technological infrastructure. All 30 fifth-grade students participated through total sampling. Data were collected via classroom observations, validated questionnaires (KMO = 0.507, p < 0.001), and documentation. Teacher implementation quality and student learning interest were assessed using percentage calculations and descriptive statistics. Teacher implementation of interactive video media achieved strong fidelity (78%,